Second-line pharmacotherapy intensification after metformin monotherapy in type 2 diabetes: a nationwide register study from Finland during 2011–2022 - Rättö, Hanna; Kurko, Terhi; Pajunen, Pia; Kastarinen, Helena (BMC, 2025)
Background
In this nationwide register study, we examined the initiation of a second-line antidiabetic medicine (ADM) among new patients receiving regular metformin monotherapy in Finland during 2011–2022. We also reflected the second-line treatment patterns on changes in the reimbursement policy, and the national type 2 diabetes (T2D) care guidelines.
Methods
Using register data on all reimbursed ADM purchases during 2010–2022, we defined nine annual cohorts of patients initiating regular metformin monotherapy during 2011–2019, each with a three-year follow-up. Descriptive methods were used to study the patterns of metformin monotherapy and second-line intensification over time. Proportional hazards models were used to analyse the take-up of the second-line ADM.
Results
The share of new patients initiating metformin use (11–13% of all metformin users) and regular metformin use (83–85% of all new metformin users) remained stable. In all cohorts, 16–19% of the patients took up a second-line ADM (median time to intensification 1.5 years). With the 2011 cohort as reference, the highest proportion of new regular metformin users taking up a second ADM (hazard ratio 1.12. 95% confidence interval 1.07 ; 1.16, P < .0001) was in the 2019 cohort. In the 2017 cohort, the proportion of patients initiating sodium-glucose cotransporter 2 inhibitors as second-line treatment surpassed those initiating dipeptidyl peptidase-4 inhibitors. The reimbursement policy restricted the use of GLP-1-analogues.
Conclusions
Second-line treatment intensification patterns over time paralleled the changes in the reimbursement system. Thus, our findings suggest that the reimbursement policy may influence the use of ADMs in Finland.